2014
DOI: 10.1016/j.jvs.2014.03.283
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgeon specialization on outcomes after ruptured abdominal aortic aneurysm repair

Abstract: Despite similar preoperative risk factors profiles, patients who were operated on by vascular surgeons had lower mortality, less frequent returns to the operating room, and decreased incidences of postoperative renal failure and cardiac events. These data add weight to the case for further centralization of vascular services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Studies with the better results (ie, mortality <35%) often abstain from reporting nonintervention rates, [26][27][28][29] thus hampering an immediate comparison of results between studies. Perioperative mortality is invariably higher (>40%) when nonintervention rates are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with the better results (ie, mortality <35%) often abstain from reporting nonintervention rates, [26][27][28][29] thus hampering an immediate comparison of results between studies. Perioperative mortality is invariably higher (>40%) when nonintervention rates are reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, optimizing patient scheduling did not influence the complication rate or the number of procedures performed per day [45,46]. There was mixed evidence regarding the surgical resident involvement: most of studies reported either no association [4,23,26,29,[61][62][63][64][65][66][67][68][69][70][71][72][73] or a negative [4,23,25,26,[63][64][65][66][67][68][74][75][76][77][78][79][80][81][82][83][84] influence regarding operative time and surgical safety, whereas few found a positive association [28,30,76]. Disturbing elements [57,[85][86][87][88]…”
Section: Discussionmentioning
confidence: 99%
“…En el tratamiento del AAAR, los cirujanos vasculares debidamente entrenados ofrecen menor mortalidad, menor tasa de reoperación y de complicaciones renales y/o cardiacas que cirujanos generales en AAAR [46][47][48] . Adicionalmente, los cirujanos vasculares declaran fuera del alcance quirúrgico a 11% de los AAAR que consultan, comparado con 64% en el caso de los cirujanos no vasculares (2 = 63,74, 1 d.f., p < 0,001) 48 .…”
Section: Especialización De Cirujano Vascularunclassified